Analisis Ketersediaan Fasilitas Kebersihan di Lingkungan Perkantoran Program Studi Manajemen Administrasi Perkantoran - Marini Marini; Marselino Saputra Mbusa; Anin Chitarisa Silitonga; Alienra Davry Nanda Kadun MT (Pusat Riset dan Inovasi Nasional, 2026)
Sanitation facilities are a fundamental element that contributes to creating a healthy, comfortable, and productive learning environment in higher education institutions. This study aims to describe the availability of sanitation facilities in the Office Administration Management Study Program, analyze the factors that influence their condition, and explore the perspectives of the academic community regarding their quality and usefulness. A qualitative descriptive approach was employed, with data collected through field observations, in-depth interviews, and documentation. The informants of this study consisted of students, lecturers, administrative staff, and facility managers. The findings reveal that sanitation facilities such as toilets, sinks, and trash bins remain inadequate in terms of quantity, physical condition, and distribution within the campus area. Several key challenges were identified, including limited financial resources, suboptimal management practices, low awareness and discipline among users, and the absence of clear and strict institutional policies related to sanitation standards. The academic community generally perceives that the available sanitation facilities do not meet the expected standards of comfort and hygiene, which may negatively affect the quality of learning experiences and academic activities. This study highlights the importance of strategic planning, adequate budget allocation, and supportive institutional policies in improving the quality of sanitation facilities. The implications of the study are expected to provide valuable input for higher education managers in formulating policies and planning facilities that are more responsive to the needs of the academic community, thereby supporting effective, professional, and sustainable educational governance.